Mammary Gland Development as a Sensitive End Point after Acute Prenatal Exposure to an Atrazine Metabolite Mixture in Female Long-Evans Rats - Enoch, Rolondo R. (National Institute of Environmental Health Sciences, 2007)
BACKGROUND: Atrazine (ATR), a widely used chlorotriazine herbicide, inhibits a number of endocrine-dependent processes, including gonadotrophin surges and mammary gland development in rats. Chlorotriazine herbicides are rapidly metabolized in plants and animals to form a group of metabolites that are detected both in the environment and in exposed animals. The extent to which these metabolites are responsible directly for the observed health effects is not understood. OBJECTIVES: Our goal was to determine if a mixture of ATR metabolites, in proportions found in the environment, might produce developmental effects in Long-Evans rats following exposure late in pregnancy. METHODS: We administered an ATR metabolite mixture (AMM) containing ATR, hydroxyatrazine, diaminochlorotriazine, deethylatrazine, and deisopropylatrazine orally to pregnant Long-Evans rats at 0.09, 0.87, or 8.73 mg/kg body weight (bw)/day, on gestation days 15–19, using 0 and 100 mg ATR/kg bw/day as negative and positive controls, respectively. RESULTS: We observed no significant effect of acute AMM exposure on body weight gain in dams during the dosing period, weight loss in pups on postnatal day (PND)4, or pubertal timing, as is seen with ATR alone. However, as with ATR, we detected delayed mammary gland development, evaluated by whole mount analysis, as early as PND4 in all treatment groups. CONCLUSIONS: Our data suggest that acute exposure to AMM at levels as low as 0.09 mg/kg bw during late pregnancy causes persistent alterations in mammary gland development of female offspring, and that these effects do not appear to be related to bw or associated with pubertal timing.